Computer-assisted semen analysis in large falcons (Falco spp.) and comparison to results of conventional semen analysis - Fischer, Dominik; Schneider, Helena; Meinecke-Tillmann, Sabine; Wehrend, Axel; Lierz, Michael W. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objective Numerous raptor species including some falcon species are facing continuous population decline in the wild and some are threatened by extinction. To support these species, captive breeding and reintroduction programs are attempted. Besides conservation, some large falcon species are commonly used in falconry and therefore bred commercially. Assisted reproduction is established in falcon breeding since the 1970s and semen analysis is an integral part to enable assessment of breeding males, inclusion or exclusion of semen donors and quality control of semen prior to artificial insemination. Conventional methods for semen analysis are widely used, but are time consuming and depend on the investigator’s experience and ability. Computer-assisted semen analysis (CASA) would offer an objective, fast and reproducible alternative, but as they have not been established in large falcon species, this was the aim of this study.Material and methods To this end, we examined in 3 breeding seasons 109 semen samples of gyr-saker hybrid falcons (n=2) and peregrine falcons (n=4) in 940 fields of view using the Minitube CASA SpermVision and compared these results to results of conventional methods of semen analysis. We used a preprogrammed setting and adapted two settings of CASA according to specific semen characteristics of falcons.Results Sperm velocity, motility and viability parameters were recorded successfully using CASA. Correlation of conventional and computer-assisted motility analysis improved during the process of adaptation of CASA settings, but both methods differed significantly due to misinterpretation of round bodies and semen impurities by CASA. Viability values of conventional and computer assisted viability analysis using SYBR-PI correlated significantly while sperm concentration did not at all.Conclusion CASA failed to replace conventional semen analysis regarding sperm motility and sperm concentration using 3 different settings, as a reliable differentiation between spermatozoa, spermatids and round bodies was not achieved.Clinical relevance Using CASA, sperm velocity parameters were measured in spermatozoa of captive-bred large falcons for the first time and may be used as orientation values.
Keywords: Spermatology; andrology; assisted reproduction; sperm analysis; raptors; birds of prey